2021
DOI: 10.3390/molecules26030759
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation and Antioxidant Activity of Globularia alypum L.

Abstract: The Moroccan flora is rich in medicinal plants that are commonly used in folk medicine for the treatment of various diseases. The present study was designed to investigate the total phenolic and flavonoid contents, as well as the antioxidant properties of leaves extracts from Globularia alypum L. colected from the Taza region in northeast Morocco. Additionally, the individual phenolics and volatiles of the extracts were also evaluated. The organic extracts of this plant were obtained by Soxhlet extraction usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
9
22
1
Order By: Relevance
“…Besides, phenolic acids, flavonoids and iridoids were also present. These compounds were identified as quinic acid derivative (1) [ 30 ], serratoside A (2) [ 31 , 32 ], fuhsioside (3) [ 33 ], calceolarioside C (4) [ 34 ], verbascoside (5) [ 35 ], tiliroside (6) [ 36 ], rhamnazin-3 O -rutinoside (7) [ 35 ], quercetin methyl galloyl-hexoside (8) [ 37 ], rosmarinic acid (9) [ 35 ], scroside B ( 10 ) [ 38 ], 2′,4″-diacetyl leucosceptoside (11) [ 39 ], acacetin 7- O -β- d -hexosyl-(1 → 2) [α- l -rhamnopyranosyl-(1 → 6)]-β- d -hexoside (12) [ 40 ], tubuloside E (13) [ 41 ], coumaric acid derivative (14) [ 42 ], 3-hydroxy-12-oleanene-28,29-dioic acid-3- O -α-L-pentosyl, 28- O - β - D -hexosyl ester (15) [ 43 ], and methyl ligstroside aglycones (16) [ 37 ]. A scheme showing most of the phytoconstituents tentatively identified in the total methanol extract of C. speciosum leaves using HPLC-ESI-MS/MS in the negative ion mode is illustrated in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, phenolic acids, flavonoids and iridoids were also present. These compounds were identified as quinic acid derivative (1) [ 30 ], serratoside A (2) [ 31 , 32 ], fuhsioside (3) [ 33 ], calceolarioside C (4) [ 34 ], verbascoside (5) [ 35 ], tiliroside (6) [ 36 ], rhamnazin-3 O -rutinoside (7) [ 35 ], quercetin methyl galloyl-hexoside (8) [ 37 ], rosmarinic acid (9) [ 35 ], scroside B ( 10 ) [ 38 ], 2′,4″-diacetyl leucosceptoside (11) [ 39 ], acacetin 7- O -β- d -hexosyl-(1 → 2) [α- l -rhamnopyranosyl-(1 → 6)]-β- d -hexoside (12) [ 40 ], tubuloside E (13) [ 41 ], coumaric acid derivative (14) [ 42 ], 3-hydroxy-12-oleanene-28,29-dioic acid-3- O -α-L-pentosyl, 28- O - β - D -hexosyl ester (15) [ 43 ], and methyl ligstroside aglycones (16) [ 37 ]. A scheme showing most of the phytoconstituents tentatively identified in the total methanol extract of C. speciosum leaves using HPLC-ESI-MS/MS in the negative ion mode is illustrated in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study clearly indicate that the TPC and TFC of I. viscosa crude extracts vary according to the solvent extraction procedure and plant origin [ 24 ]. Additionally, numerous studies have shown the antioxidant capacity of plants to constructively correlate with TPC and TFC [ 25 , 26 , 27 , 28 ]. Phenolic acids and flavonoids are better extracted with hydrophilic solvents, whereas less hydrophilic ones such as chloroform may extract more lipophilic components such as triterpenoids that preferentially inhibits 5-lipoxygenase activity [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation of the mixture for 10 min at 3000 rpm, 2.5 mL were collected from the upper layer, mixed with 2.5 mL of distilled water, and 0.5 mL of FeCl 3 (0.1%) and the absorbance was measured at 700 nm using a spectrophotometer. Tocopherol was used as a standard [ 24 ].…”
Section: Methodsmentioning
confidence: 99%